Essential and toxic elements in seaweeds for human consumption. Issue 3 (1st February 2016) - Desideri, D.; Cantaluppi, C.; Ceccotto, F.; Meli, M. A.; Roselli, C.; Feduzi, L.
ABSTRACT: Essential elements (K, Ca, P, S, Cl, Mn, Fe, Cu, Zn, Ni, Br, and I) and nonessential or toxic elements (Al, Ti, Si, Rb, Sr, As, Cd, Sn, and Pb) were determined by energy-dispersive polarized x-ray fluorescence spectrometry in 14 seaweeds purchased in local specialty stores in Italy and consumed by humans. The differences in elements between the algae species reached up to 2–4 orders of magnitude. Lithothamnium calcareum showed the highest levels of Ca, Al, Si, Fe, and Ti. Palmaria palmata showed the highest concentrations of K, Rb, and Cl. The highest content of S was in Chondrus crispus. Laminaria digitata contained the highest concentrations of total As, Cd, Sn, Br, and I. The highest concentration of Zn was in Chlorella pyrenoidosa. Ulva lactuca displayed the highest levels of Cu, Ni, Mn, and Pb. Iodine levels ranged from 3.4 in Chlorella pyrenoidosa to 7316 mg/kgdry in Laminaria digitata . The nutrimental importance of essential elements was assessed using nutritional requirements. The results showed that the consumption of algae might serve as an important source of the essential elements. Health risk due to the toxic elements present in seaweed was estimated using risk estimators. Total As, Cd, and Pb concentrations ranged from <1 to 67.6, to 7.2 and to 6.7 mg/kgdry respectively; therefore, their contribution to total elemental intake does not appear to pose any threat to the consumers, but the concentrations of these elements should be controlled to protect the consumer against potential adverse health risks.